Editorial (Australian and International Journal of Rural Education, 2012)
Welcome to the second issue of the Australian and International Journal of Rural Education for 2012. In this issue we present nine papers from national and international authors. The importance of rural and remote issues in the school sector, the university sector, professional practice and community are raised by a wide range of esteemed authors.